Sustainable Managerial Practices in Implementation of Circular Economy Concepts in Romanian Agriculture - Dragos Horia Buhociu; Florin Marian Buhociu; Laura Zugravu; Gheorghe Adrian Zugravu (Journal of Agriculture and Rural Development Studies, 2024)
This study examines the integration of sustainable managerial practices in the implementation of circular economy concepts within Romanian agriculture. The research highlights the growing importance of transitioning from traditional linear models to circular approaches that promote resource efficiency, waste reduction, and environmental sustainability. By analyzing current practices and identifying key challenges, the study provides insights into how Romanian agricultural businesses can adopt circular economy principles to enhance their sustainability and competitiveness. The findings suggest that while there is increasing awareness and adoption of circular practices, there is a need for stronger policy support, technological innovation, and knowledge transfer to fully realize the potential of the circular economy in Romania's agricultural sector. The study concludes with recommendations for policymakers and agricultural managers to foster a more sustainable and resilient agricultural system in Romania.